Using collagenase to treat Dupuytren’s disease: a hypothetical cost benefit analysis - Ryan Livingston; Michael Wagels; Alicia Heald (Australasian Journal of Plastic Surgery)
**Background**: Dupuytren’s disease is a disorder of abnormal collagen production that may manifest in the palmar fascia. Treatment options vary according to clinical circumstances but surgical fasciectomy remains the gold standard. Collagenase, an enzyme produced by clostridium histolyticum (CCH), is a relatively new injection able to cleave collagen strands in vitro. While the drug is not yet available on the Pharmaceutical Benefits Scheme (PBS), its side effect profile and risk of recurrence are comparable to fasciectomy in appropriately selected patients. In this study, we aimed to demonstrate the safety and cost-effectiveness of collagenase for the treatment of Dupuytren’s disease. **Method**: Twenty-five patients at our hospital received collagenase injections for treatment of their Dupuytren’s disease. Data from this cohort was compared to a hypothetical group extrapolated from the literature. **Results**: Surgical treatment, excluding outpatient visits, costs on average AU$5852 per patient and collagenase costs AU$1176 per patient (gross cost difference AU$4676). Moderating this cost difference by the effect of complications using the incremental cost effectiveness ratio, the cost saving is AU$1137.71 per unit decrease in complications with collagenase treatment. Surgical fasciectomy has a lower risk of recurrence than collagenase but costs up to AU$543 more for patients for whom the condition does not recur within five years of treatment. In our cohort, 25 patients had 31 cords injected with collagenase. All but two patients achieved full range of motion of their affected joint and 20 per cent sustained minor skin tears requiring dressings. **Conclusion**: This analysis suggests that the investment of public health funds in the treatment of suitable patients with collagenase should produce a substantial cost saving without increasing the risk of complications.